Application of Design Patterns for modern JavaScript to solve real world problems - Arthur dos Santos Dias (2018)
The aim of this Bachelor Thesis is to verify the usability of Design Patterns applied to Modern JavaScript in order to solve Common Problems in the industry. First an overview of the current state of JavaScript is presented. Then a closer look on Design Patterns is made, with focus on specific design patterns which can be optimized with modern JavaScript. After that a generator for design patterns is proposed and analyzed. Finally a few tests with real world scenarios are made using the generator, and a conclusion by measuring the benefits of using modern JavaScript to apply Design Patterns versus the classical methods.